984 Changing the Management of Epistaxis in the Covid-19 Era. (12th October 2021) - Kerr, B; Dalton, J; Stewart, R; Stewart, R; McGahey, D
Abstract: Aim: Epistaxis in the Covid pandemic is a concerning problem facing otolaryngologists due to high droplet concentration and increased virulence in nasal secretions. Furthermore, safe ambulation of patients reduces Covid exposure and preserves essential resources. This study assessed the implementation of ENT UK recommended altered epistaxis management during the Covid pandemic. Method: Patients presenting to a medium-sized community hospital with unrelenting epistaxis had a rapid rhino (RR) inserted. Able patients were ambulated and given an appointment for RR removal. Previously all patients were admitted. A comparative retrospective analysis of patients referred with epistaxis was conducted using electronic care records from March – August 2019 versus the same period in 2020. Follow-up phone-call was also employed. Admissions, bed days, RR complications and patient satisfaction was assessed. Data was analysed student t -tests. Results: A significant reduction in admissions (n = 91; P < 0.001) and bed days (n = 104; P < 0.001) was observed. Only 2 out of the 68 patients ambulated required medical assistance prior to their scheduled appointment (3%; P < 0.001). The majority of patients were satisfied (91%) and reported no bleeding (94%). No RR dislodgement occurred (0%) and most patients were pleased to avoid admission (92%). 70% of patients reported severe pain following RR insertion. Conclusions: Ambulation of patients presenting to ED with unrelenting epistaxis managed with RR insertion is a safe alternative to previous practice with few complications. Furthermore, patients are largely satisfied although reported severe pain post RR insertion needs addressed. Finally, this altered management reduces contact and preserves resources as our hospitals face overwhelming pressures.